Long-Term Effects from a School-Based Trial Comparing Interpersonal Psychotherapy-Adolescent Skills Training to Group Counseling. (29th March 2019) - Young, Jami F.; Jones, Jason D.; Sbrilli, Marissa D.; Benas, Jessica S.; Spiro, Carolyn N.; Haimm, Caroline A.; Gallop, Robert; Mufson, Laura; Gillham, Jane E.
Abstract : Adolescence represents a vulnerable developmental period for depression and an opportune time for prevention efforts. In this study, 186 adolescents with elevated depressive symptoms ( M age = 14.01, SD = 1.22; 66.7% female; 32.2% racial minority) were randomized to receive either Interpersonal Psychotherapy–Adolescent Skills Training (IPT-AST; n = 95) delivered by research clinicians or group counseling (GC; n = 91) delivered by school counselors. We previously reported the short-term outcomes of this school-based randomized controlled trial: IPT-AST youth experienced significantly greater improvements in depressive symptoms and overall functioning through 6-month follow-up. Here, we present the long-term outcomes through 24 months postintervention. We examined differences in rates of change in depressive symptoms and overall functioning and differences in rates of depression diagnoses. Youth in both conditions showed significant improvements in depressive symptoms and overall functioning from baseline to 24-month follow-up, demonstrating the efficacy of school-based depression prevention programs. However, the two groups did not differ in overall rates of change or in rates of depression diagnoses from baseline to 24-month follow-up. Although IPT-AST demonstrated advantages over GC in the short term, these effects dissipated over long-term follow-up. Specifically, from 6- to 24-month follow-up, GC youth showed continued decreases in depressive symptoms, whereas IPT-AST youth showed a nonsignificant increase in symptoms. GC youth remained relatively stable in overall functioning, whereas IPT-AST youth experienced a small but statistically significant worsening in functioning. This study highlights the potential of school-based depression prevention efforts and the need for further research.